Aplikasi Pemesanan Lapangan Futsal Berbasis Android Pada Kejora Futsal 88 Menggunakan Metode FCFS - Matondang, Zekson Aizona; Malau, Kevin Hesekiel (KAKIFIKOM : Kumpulan Artikel Karya Ilmiah Fakultas Ilmu Komputer, 2025)
As technology develops, conventional futsal court booking systems that require customers to come in person are becoming inefficient. The Android-based booking application for Kejora Futsal 88, using the First Come First Served (FCFS) method, is designed to address this issue. This application makes it easier for customers to book courts online in real-time, without having to visit the physical location. This study aims to reduce paper usage and improve service by utilizing the FCFS method, which ensures a more structured and timely booking process.